Sistem Pendukung Keputusan Pemilihan Personil untuk Pengamanan Infrastruktur IT TNI Angkatan Laut Menggunakan Metode Vikor - Mohammad Faried Rahmat; Abdillah Imam Julianto (Universitas Merdeka Malang, 2023)
The selection of personnel for the IT Infrastructure Section of the Indonesian Navy has the duty and responsibility to protect IT Infrastructure in the Indonesian Navy in protecting infrastructure assets from cyber security attacks which are increasingly being carried out by irresponsible parties. In carrying out their duties, proper staffing data is required according to the field and in accordance with the criteria related to Engineering, Tactics and Strategic. Therefore, this research developed a decision support system to analyze and select appropriate personnel in the field and according to the criteria to be able to develop and maintain IT Infrastructure in the Indonesian Navy. The method used in this study is to use the Vikor method. with research subjects are IT Infrastructure personnel in the Indonesian Navy. the calculation results from the Vikor method with Technical, Tactical and Strategic criteria will show appropriate personnel with qualified capabilities in protecting IT Infrastructure in the Indonesian Navy from Cyber attacks.